Smart order tracker : Enhancing bakery operations with VBA - Suhaila, Bahrom (Academica Press Solution, 2024)
This project introduces an innovative graphical user interface (GUI)-based order tracking system for home bakery owners, developed using VBA. The GUI simplifies the order process, enabling efficient input, management, and tracking of customer orders. Designed with user-friendliness, it allows users to enter order details and automatically update records quickly. The system ensures accurate record-keeping and streamlines order processing, significantly reducing manual errors and enhancing operational efficiency. By integrating this automated solution, users can manage orders, track sales trends, and improve customer service to drive business growth and sustainability.